A CMOS 0.18 [my]m 600 MHz clock multiplier PLL and a pseudo-LVDS driver for the high speed data transmission for the ALICE Inner Tracking System front-end chip - Lattuca, Alessandra; Mazza, G.; Rinella, G. Aglieri; Cavicchioli, C.; Chanlek, N.; Collu, A.; Degerli, Y.; Dorokhov, A.; Flouzat, C.; Gajanana, D.; Gao, C.; Guilloux, F.; et al. (Journal of Instrumentation, 2016)
This work presents the 600 MHz clock multiplier PLL and the pseudo-LVDS driver which are two essential components of the Data Transmission Unit (DTU), a fast serial link for the 1.2 Gb/s data transmission of the ALICE inner detector front-end chip (ALPIDE). The PLL multiplies the 40 MHz input clock in order to obtain the 600 MHz and the 200 MHz clock for a fast serializer which works in Double Data Rate mode. The outputs of the serializer feed the pseudo-LVDS driver inputs which transmits the data from the pixel chip to the patch panel with a limited number of signal lines. The driver drives a 5.3 m-6.5 m long differential transmission line by steering a maximum of 5 mA of current at the target speed. To overcome bandwidth limitations coming from the long cables the pre-emphasis can be applied to the output. Currents for the main and pre-emphasis driver can individually be adjusted using on-chip digital-to-analog converters. The circuits will be integrated in the pixel chip and are designed in the same 0.18 μm CMOS technology and will operate from the same 1.8 V supply. Design and test results of both circuits are presented.
Gesehen am 16.06.2020
Im Titel ist "my" als griechischer Buchstabe dargestellt